Testing temporal disaggregation - Christian Müller (ETH Zurich, KOF Swiss Economic Institute, 2006)
Economists and econometricians very often work with data which has been temporally disaggregated prior to use. Hence, the quality of the disaggregation clearly affects the quality of the analyses. Building on Chow and Lin's (1971) disaggregation model this paper proposes a new estimation approach and a specification test which assesses the quality of the disaggregation model. An advantage of the proposal is that estimation and testing can both be pursued using the aggregated data while the standard method requires a mixture of high and low frequency data. A small simulation study shows that the test indeed provides useful information.
Keywords: F31; F47; C53; 330; temporal disaggregation; restricted ARMA; Aggregation; ARMA-Modell; Ökonometrisches Modell